TINGKAT KEPERCAYAAN KHALAYAK ATAS BERITA LIFESTYLE DI MEDIA SOSIAL INSTAGRAM “USSFEEDS” (SURVEY KUANTITATIF DESKRIPTIF TINGKAT KEPERCAYAAN KHALAYAK FOLLOWERS INSTAGRAM USSFEEDS) - Zahra, Amira Fatimatuz; Mulyani, Henny Sri; Kusmayadi, Ika Merdekawati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research departs from the problem of the rise of online media that disseminates information using fairly short captions through social media. The number of new media that have emerged also affects the flow of information that is increasingly swift to the public. This study was conducted to determine the level of public trust in news from non-mainstream media USSFeeds on Instagram by containing four dimensions of trust, namely (1) based on selectivity of news topics, (2) based on selectivity of news facts, (3) the level of public trust in accurate depiction, and (4) the level of public trust in journalistic judgment. This research approach uses descriptive quantitative research methods. The results obtained from this study found that in terms of selectivity of news topics, audiences rely on the